ANALISIS DAN IMPLEMENTASI SISTEM INFORMASI PENGOLAHAN DATA LEGER JALAN BERBASIS WEB PADA CV. ADHIHANMAN TATA RANCANG BANJARMASIN - Auliya Rahman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
In the current era of free competition, the speed of processing and delivering information has a very important role for every agency or company, especially in offices that have a high level of routine and have a lot of data that must be processed. CV. Adhihanman Banjarmasin Design System is a company that handles documents that contain data and information about the development of a road. While in data processing, leger roads still use conventional methods such as ledgers. Therefore it is necessary to build a computerized information system so that data and information or reports can be presented faster, precisely, and efficiently. The leger road information system is made to facilitate data processing. It is expected that this new system can reduce the work process as much as possible. This information system is made by observation and documentation methods from data collection, data analysis, design to system creation, and using PHP applications using a MySQL database.